2021
DOI: 10.3991/ijim.v15i06.20675
|View full text |Cite
|
Sign up to set email alerts
|

Digital Healthy Lifestyle Application for UUM Computer User

Abstract: <span>A computer is a vital tool for UUM community in doing routine jobs and activities. Spending many hours using a computer without breaks can cause bad effect on users’ health. Inappropriate computer use can cause muscle and joint pain, overuse injuries of the shoulder, arm, wrist or hand, and eyestrain. Fortunately, this pain and misery can be avoided with only a few simple routines. Therefore, a short break from using a computer is necessary. The break could be filled with a short and simple exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In our present study, mobile phone found to be the most popular device used by the university students with an average time spent of 10 hours a day. Similar time spent of average 10 hours a day was reported among computer users in a study conducted in University Utara Malaysia [21]. Sharan, Mohandoss [22] stated that smart phones and other digital devices that promoted the use of only one finger (or predominant thumb) while texting, were linked with a higher occurrence of musculoskeletal symptoms.…”
Section: Musculoskeletal Symptoms Associated With Hand Position Of Digital Devices Usesupporting
confidence: 54%
“…In our present study, mobile phone found to be the most popular device used by the university students with an average time spent of 10 hours a day. Similar time spent of average 10 hours a day was reported among computer users in a study conducted in University Utara Malaysia [21]. Sharan, Mohandoss [22] stated that smart phones and other digital devices that promoted the use of only one finger (or predominant thumb) while texting, were linked with a higher occurrence of musculoskeletal symptoms.…”
Section: Musculoskeletal Symptoms Associated With Hand Position Of Digital Devices Usesupporting
confidence: 54%
“…In the education sector [14][16], among others design and development of a simple content management system for learning called the EMasters [17], PAUD monitoring application [18]. In the health sector there are several studies [19][21], including developed of the healthy phone is a mobile medical emergency call apps that can help people with hearing impaired when in emergency situations [22].…”
Section: Introductionmentioning
confidence: 99%